Performance on Financial Accounting Course: Evidence from Kolej Matrikulasi Kedah - Zuraini, Zakariah (2011)
This study explores the factors that influence Kolej Matrikulasi Kedah accounting students’ performance in the Financial Accounting. The performance of the matriculation students in this study is measured by their end semester results in the Financial Accounting. In this study, the student demographic profile, subject taken by the students in secondary level are used as variables for the students’ performance in the Financial Accounting. The result shows that the variables do explain the variance in the students’ performance in the Financial Accounting. This research project attempted to determine if there was a relationship between mathematics subjects in SPM level accounting students’ performance in Financial Accounting. The result of the study will be useful to the academic communities, the public and other interested parties who are interested in improving students’ performance during their period of study in the secondary level and matriculation.